De professor para professor-coordenador: sentimentos e emoções envolvidos na mudança - Groppo, Cristiane (2007)
This research intends to identify feelings and emotions present in the teacher who becomes a coordinator teacher in a public school of the state of São Paulo not only in the period that precedes the beginning of his activities but also in the first months he is in the new position. Besides it tries to understand the situations of life that lead to these feelings and emotions. My studies give priority to affectionate matters and emphasize the reflections on preparation of the teacher who will be a coordinator; in addition to these methodological purposes they examine the support and orientation he is given at the commencement of his new job. The basis for my analyses was provided by Henry Wallon´s theory, whose main subject includes three important elements found in the composition of the human character: affectionateness, cognition and movement. Different instruments were utilized to collect the data: an interview with five coordinator teachers just employed in the position in public schools located in the outskirsts of the city of São Paulo; other documents and observations of the context in which the data are considered as well. After the analysis of the data I came to the conclusion that before being a coordinator, the feelings that prevail in the teacher are those of satistaction, agreeable sensation. As time goes by, on the contrary, little by little, he begins to feel uncomfortable when he is about to start the new job. The data showed that he feels secure and important to get the position of coordinator. But after some months in the occupation he feels insecure, disappointed, discouraged and frustratred. As a rule, disagreeable feelings have its origin in facts of life that interfere substantially in the activity of the coordinator teacher, what is materialized in the lack of specific orientation for the coordinator and the absence of the required support that may give him skills to solve many situations of conflict that happen in the daily life of his school. Key words: affectionate dimension Wallonian theory coordinator teacher.